2003
DOI: 10.1074/jbc.m304479200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Sodium-dependent Depolarization by External Calcium Removal in Human Sperm

Abstract: Removal of external calcium with EGTA (from 2.5 mM to nanomolar levels) caused a remarkable depolarization in human sperm. This depolarization was initially fast. It was followed by a slow phase that brought the V m to values of over 0 mV in 1-2 min. The slow and sustained phase correlated with a sustained decrease in intracellular calcium. However, calcium removal still induced depolarization in sperm with enhanced intracellular calcium (induced by progesterone), indicating that the sustained depolarization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…This characteristic of CatSper, which is a result of divalent cation binding within the channel pore, can explain earlier observations which showed that divalent cation-free (or depleted) medium causes enhanced Na + influx and depolarization of human sperm (Gonzáles-Martinez, 2003; Torres-Flores et al , 2011) and can also account for the loss of K + versus Na + selectivity that we observed in medium devoid of divalent cations medium. However, NNC55-0396 and mibefradil, structurally related compounds that block CatSper, suppressed the hyperpolarizing K + recorded under standard (physiological) conditions.…”
Section: Discussionsupporting
confidence: 83%
“…This characteristic of CatSper, which is a result of divalent cation binding within the channel pore, can explain earlier observations which showed that divalent cation-free (or depleted) medium causes enhanced Na + influx and depolarization of human sperm (Gonzáles-Martinez, 2003; Torres-Flores et al , 2011) and can also account for the loss of K + versus Na + selectivity that we observed in medium devoid of divalent cations medium. However, NNC55-0396 and mibefradil, structurally related compounds that block CatSper, suppressed the hyperpolarizing K + recorded under standard (physiological) conditions.…”
Section: Discussionsupporting
confidence: 83%
“…Li ϩ can replace Na ϩ ; thus, these findings suggest that a Na ϩ -and Li ϩ -permeable electrogenic pathway may be present in mammalian sperm (19). The present work explores this later possibility.…”
mentioning
confidence: 76%
“…In light of the results presented here, if calcium influx through VDCC contributes to resting [Ca 2ϩ ] i , the small but biologically significant increase in [Ca 2ϩ ] i observed during capacitation could be related to the VDCC stimulation reported here. Other putative non-voltagedependent calcium channels have been considered as mechanisms to set the resting [Ca 2ϩ ] i (11).…”
Section: Discussionmentioning
confidence: 99%
“…There is a linear relationship between the fractional change of diSC 3(5) fluorescence, f Ϫ fo/fo (where fo is fluorescence in the presence of valinomycin addition and f are actual fluorescence values), and E k (23). Consequently, f can be converted to V m according to the following equation (11): Vm ϭ f/mf o Ϫ 1/m Ϫ b/m, where m and b are parameters of the linear calibration curve, that is, the slope and the fractional change of fluorescence at 0 mV, respectively.…”
Section: Methodsmentioning
confidence: 99%